MODELING THE ALLOCATION OF SOURCES OF FUNDING IN BANKS - A. Zh. Bakashbayev, (Academic Journal of Physical and Chemical Sciences, 2019)
Funding in banks has a significant role, since, unlike companies, banks are 90 percent functioning at the expense of borrowed funds. On this basis, the attracted resources are the main source of funding for the activities of second-tier banks. Moreover, when redistributing funds in a bank, namely directing certain attracted resources to active operations, the order of this redistribution is important. That is, what raised funds should be used as sources of funding for certain active operations of banks. The solution of this kind of problem in banks is possible with the use of linear and dynamic programming. The article presents an example of the use of mathematical statistics to determine the optimization of the allocation of funding for relevant active operations that can bring profit to the bank.